METHODS FOR MEMORIZING TAHFIDZ QUR'AN IN CHILDREN AND THE SEARCH FOR IDENTITY (Study in the Salafi Community of Ngawi Regency) - Sriyanto, Agus (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to analyze the Tahfidz Al-Qur'an memorization method for children in the Salafi Community of Ngawi Regency and how this method contributes to children's search for identity. Using a qualitative approach, data was collected through in-depth interviews, observation and documentation studies. The research results show that the memorization method applied does not only focus on cognitive aspects but also on the formation of children's character and self-identity. Apart from that, there is a significant relationship between the memorization method applied and increased self-confidence and understanding of religion in children.